The Sherrods - McCutcheon, George Barr, 1866-1928; Williams, C. D. (Charles D.), 1875-1954 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Sherrods" by George Barr McCutcheon is a novel written in the early 20th century. The narrative centers around the lives of Justine Van and Jud Sherrod, two young lovers from a rural background who navigate the challenges of poverty and societal expectations after their marriage. The book explores themes of love, ambition, and the tension between country life and the allure of the city. At the start of the story, we meet Justine and Jud on the eve of their wedding. Their tender interaction hints at a deep emotional connection, yet there is an underlying tension due to another suitor, 'Gene Crawley, whose aggressive behavior threatens their happiness. As they transition from a life of youthful dreams to the responsibilities of marriage, the opening chapters set the stage for conflicts that will test their bond, including the ominous presence of Crawley, who harbors dark intentions. The unfolding dynamics between the characters highlight the purity of Justine and Jud's love against the backdrop of adversities, hinting at themes of resilience in the face of societal challenges. (This is an automatically generated summary.)
Release date is 2011-02-24
Produced by Al Haines
Keywords: Bigamy -- Fiction